Daily-Life Physical Activity of Healthy Young Adults Associates With Function and Structure of the Hippocampus - Seoane, Sara; Ezama, Laura; Janssen, Niels (Frontiers in Human Neuroscience, 2022)
Previous research on Physical Activity (PA) has been highly valuable in elucidating how PA affects the structure and function of the hippocampus in elderly populations that take part in structured interventions. However, how PA affects the hippocampus in younger populations that perform PA during daily-life activities remains poorly understood. In addition, this research has not examined the impact of PA on the internal structure of the hippocampus. Here we performed a cross-sectional exploration of the way structural and functional aspects of the hippocampus are associated with habitual PA performed during work, leisure time and sports in the daily lives of healthy young adults ($n = 30$; 14 female; mean age = 23.9 y.o.; SD = 7.8 y.o.). We assessed PA in these three different contexts through a validated questionnaire. The results show that PA performed during work time correlated with higher subicular volumes. In addition, we found that PA changed functional connectivity between a location in middle/posterior hippocampus and regions of the default mode network, and between a location in anterior hippocampus and regions of the somatomotor network. No statistical effects of PA performed during leisure time and sports were found. The results generalize the impact of PA to younger populations and show how PA performed in daily-life situations correlates with the precise internal structure and functional connectivity of the hippocampus.